2011
DOI: 10.1097/wnp.0b013e31821213eb
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Spike and Waves During Sleep and Electrical Status Epilepticus in Sleep

Abstract: Continuous spike and waves during sleep is an age-related epileptic encephalopathy that presents with neurocognitive regression, seizures, and an EEG pattern of electrical status epilepticus during sleep. Patients usually present around 5 years of age with infrequent nocturnal unilateral motor seizures that progress within 1 to 2 years to a severe epileptic encephalopathy with frequent seizures of different types, marked neurocognitive regression, and an almost continuous spike-wave EEG pattern during slow-wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(115 citation statements)
references
References 127 publications
(216 reference statements)
3
109
0
3
Order By: Relevance
“…According to Loddenkemper et al (2011) fine and gross motor skills may also be observed. Dystonia, dyspraxia, ataxia, and unilateral Several studies attempted to correlate nuropsychological deficits in chidhood regional idiopathic hyperexcitability syndromes.…”
Section: Relations With Neuropsychological Impairmentmentioning
confidence: 99%
See 4 more Smart Citations
“…According to Loddenkemper et al (2011) fine and gross motor skills may also be observed. Dystonia, dyspraxia, ataxia, and unilateral Several studies attempted to correlate nuropsychological deficits in chidhood regional idiopathic hyperexcitability syndromes.…”
Section: Relations With Neuropsychological Impairmentmentioning
confidence: 99%
“…Not only the electro-morphology was considered to be "spike-and-wave" but the recent interpretations about the pathomechanism of the discharges also went back to the classical generalized spike wave pattern. For example, Loddenkemper et al (2011) and Sánchez Fernández et al (2012) trying to explain the association of ESES and early thalamic lesion, refer to the Steriade model of spike-wave network, related to the interrelationships within the cortico-thalamic system. Similarly, Tassinari et al (2012) relies on the secondary bilateral synchrony mechanism which was assumed to work classically (Tükel and Jasper, 1952) by involving secondarily thalamic and thalamo-cortical circuitry.…”
Section: Terminological and Conceptual Chaos Around Eses Cswsmentioning
confidence: 99%
See 3 more Smart Citations